Writing signs : the Fatimid public text - Bierman, Irene A. (Berkeley : University of California Press, 1998)
Explores the complex relationship between alphabet and language, as well as the ways the two elements are socially defined by time and place. The author focuses on the Eastern Mediterranean in the 6th-12th centuries, particularly Cairo's Fatimid dynasty of 969-1171.
Initial Considerations -- Signing the Community -- The Fatimid Public Text and the Sign of Ismàilism -- The Fatimid Public Text in a Changing Political Climate.
Includes bibliographical references (pages 191-205) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Fatimiden -- 909-1171; Fatimiden; Written communication -- Egypt -- History; Arabic language -- Social aspects; Fatimites -- Language; Communication écrite -- Égypte -- Histoire; Arabe (Langue) -- Aspect social; Fātimides -- Langage; LANGUAGE ARTS & DISCIPLINES -- Literacy; Arabic language -- Social aspects; Fatimites -- Language; Written communication; Egypt; Beschilderung; Kairo; Arabisch schrift; Fatimiden; Philology & Linguistics; Languages & Literatures; Geschichte 969-1171.; History